Supply chain management strategy, planning, and operation - Chopra, Sunil (Pearson, 2013)
Supply Chain Management illustrates the key drivers of good supply chain management in order to help students understand what creates a competitive advantage. This text also provides strong coverage of analytic skills so students can gauge the effectiveness of the techniques described in the text.